Nanomedicine-Based Therapeutics to Combat Acute Lung Injury - Bian S (Dove Medical Press, 2021)
Shuai Bian,1 Hongfei Cai,1 Youbin Cui,1,* Wanguo Liu,2,* Chunsheng Xiao3 1Department of Thoracic Surgery, The First Hospital of Jilin University, Changchun, 130021, People’s Republic of China; 2Department of Orthopedic Surgery, China-Japan Union Hospital of Jilin University, Changchun, 130033, People’s Republic of China; 3Key Laboratory of Polymer Ecomaterials, Changchun Institute of Applied Chemistry, Chinese Academy of Sciences, Changchun, 130022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Youbin CuiDepartment of Thoracic Surgery, The First Hospital of Jilin University, Changchun, 130021, People’s Republic of ChinaEmail cuiyb@jlu.edu.cnWanguo LiuDepartment of Orthopedic Surgery, China-Japan Union Hospital of Jilin University, Changchun, 130033, People’s Republic of ChinaEmail liuwanguo6016@jlu.edu.cnAbstract: Acute lung injury (ALI) or its aggravated stage acute respiratory distress syndrome (ARDS) may lead to a life-threatening form of respiratory failure, resulting in high mortality of up to 30– 40% in most studies. Although there have been decades of research since ALI was first described in 1967, the clinical therapeutic alternatives for ALI are still in a state of limited availability. Supportive treatment and mechanical ventilation still have priority. Despite some preclinical studies demonstrating the benefit of pharmacological interventions, none of these has been proved completely effective to date. Recent advances in nanotechnology may shed new light on the pharmacotherapy of ALI. Nanomedicine possesses targeting and synergistic therapeutic capability, thus boosting pharmaceutical efficacy and mitigating the side effects. Currently, a variety of nanomedicine with diverse frameworks and functional groups have been elaborately developed, in accordance with their lung targeting ability and the pathophysiology of ALI. The in-depth review of the current literature reveals that liposomes, polymers, inorganic materials, cell membranes, platelets, and other nanomedicine approaches have conferred attractive therapeutic benefits for ALI treatment. In this review, we explore the recent progress in the study of the nanomedicine-based therapy of ALI, presenting various nanomedical approaches, drug choices, therapeutic strategies, and outcomes, thereby providing insight into the trends.Keywords: acute lung injury, acute respiratory distress syndrome, drug delivery, nanoparticle, nanomedicine